2015
DOI: 10.1038/ismej.2015.213
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic oxidation of methane associated with sulfate reduction in a natural freshwater gas source

Abstract: The occurrence of anaerobic oxidation of methane (AOM) and trace methane oxidation (TMO) was investigated in a freshwater natural gas source. Sediment samples were taken and analyzed for potential electron acceptors coupled to AOM. Long-term incubations with 13C-labeled CH4 (13CH4) and different electron acceptors showed that both AOM and TMO occurred. In most conditions, 13C-labeled CO2 (13CO2) simultaneously increased with methane formation, which is typical for TMO. In the presence of nitrate, neither metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 77 publications
2
78
1
Order By: Relevance
“…Environmental studies also suggest that ANME-2D are involved in SO 4 2--dependent AOM (Timmers et al 2016(Timmers et al , 2017. However, our results showed that AOM organisms did not use inorganic EAs in the study sediments.…”
Section: Microbial Community Structurecontrasting
confidence: 55%
See 3 more Smart Citations
“…Environmental studies also suggest that ANME-2D are involved in SO 4 2--dependent AOM (Timmers et al 2016(Timmers et al , 2017. However, our results showed that AOM organisms did not use inorganic EAs in the study sediments.…”
Section: Microbial Community Structurecontrasting
confidence: 55%
“…The independency of the potential CH 4 oxidation from the net potential CH 4 production in anaerobic conditions would suggest that CH 4 oxidation mainly took place through AOM at the profundal site. In contrast, the concurrent EA-induced decrease in the potentials of both CH 4 oxidation and net CH 4 production would suggest that CH 4 oxidation mainly took place through TMO at the littoral site (Table 2) (Moran et al 2005;Meulepas et al 2010;Timmers et al 2016). However, the results of the CH 2 F 2 experiments necessitate a more in-depth discussion of the contribution of the different processes to CH 4 oxidation.…”
Section: Microbial Community Structurementioning
confidence: 78%
See 2 more Smart Citations
“…HS can theoretically promote AOM, as they can serve as terminal electron acceptors for microbial respiration (18,19) and have a higher redox potential than sulfate (20). However, compelling evidence demonstrating AOM driven by the microbial reduction of NOM present in anoxic environments remains elusive (21,22).…”
Section: Importancementioning
confidence: 99%